Soil nitrogen heterogeneity in a Dehesa ecosystem (Plant and Soil, 2000)
The Dehesa are savannah-like ecosystems that occupy extensive areas in the mediterranean regions of Southern Spain and Portugal. The changes in the soil nitrogen (N) potential mineralisation rate, microbial biomass-N and available mineral N in soils were studied over 1 year in a Dehesa ecosystem, in the SW of Spain. The temporal variability of soil samples was compared by using the coefficient of variation of samples taken on a monthly basis. Spatial variability of the soil samples was measured by comparing the variograms generated with geostatistical techniques. The potential N mineralisation reached a maximum in the spring and summer samples, and a minimum in the autumn. However, the soil NHC 4 , NO 3 and microbial biomass-N showed maximum levels in winter, compared with minimum levels in the spring and summer. The potential mineralisation rate showed a higher temporal variability in the samples taken under tree canopies, due to highest maximum and similar minimum levels reached during the sampling period. The potential mineralisation rate, microbial biomass-N and soil mineral N were higher under the tree canopies than in the open grassland. The spatial distribution of the soil organicmatter and available NHC 4 was strongly influenced by tree canopy size. The semivariograms were adjusted to a spherical model, indicating a maximum NHC 4 variability at a certain distance from the tree crown diameter. The same was not the case for the spatial distribution of the soil NO 3 from the tree crown. Our results indicate that the tree component of a Dehesa ecosystem is a major influence in the spatial and temporal heterogeneity of soils.